PROSES TOREFAKSI TANDAN KOSONG KELAPA SAWIT UNTUK KANDUNGAN HEMISELULOSA DAN UJI KEMAMPUAN PENYERAPAN AIR - Anton Irawan; Tubagus Riadz; Nurmalisa Nurmalisa (Reaktor, 2015)
EMPTY FRUIT BUNCHES TORREFACTION FOR HEMICELLULOCE CONTENT ANDWATER ABSORPTION TEST. Biomass is organic material resulting from the process ofphotosynthesis. Biomass can be produced directly as product or waste from the processing ofagricultural or plantation. Indonesia is a country that produces biomass in very large quantities. Oneof the largest biomass resulting from the proceessing of palm oil is oil palm empty fruit bunches(EFB). Basically, the EFB has a low energy content and easily absorbs water. With higher productionof palm oil, the EFB has potential as a good quality fuel and need early treatment to maintain thequality of the EFB. Torrefaction was one of thermal treatments with process temperature around200-350 ° C in the absence oxygen condition. By torrefaction, the EFB has a high energy content anddecrease the water absorption. With low water absorption, EFB will have benefit in the storage thathas high humidity such as Indonesia. The variables that varied for EFB torrefaction was thetemperature (250-350 ° C) and the holding time (15-60 minutes) to produce the high quality solid fuelfrom EFB. Analysis product in this study was proximate analysis, water absorption, and hemicelluloseand caloric value. The results showed that the higher temperature and longer time torrefaction hadhigher calorific value, the hemicellulose content decreased thereby increasing hydrophobicity. Also,the torrefaction EFB can increase the calorific value around 30%. Keywords: calorific value; empty fruit bunches (EFB); hemicellulose; hydrophobic; torrefaction AbstrakBiomassa merupakan material organik yang dihasilkan dari proses fotosintesis. Biomassa dapatdihasilkan secara langsung sebagai produk atau limbah dari pengolahan hasil pertanian atauperkebunan. Indonesia merupakan negara kaya akan biomasa dengan jumlah yang melimpah. Salahsatu biomassa dengan jumlah yang melimpah adalah limbah yang dihasilkan dari pengolahan bijikelapa sawit antara lain tandan kosong kelapa sawit (TKKS). Pada dasarnya, TKKS memilikikandungan energi rendah serta mudah menyerap air. Dengan jumlah biomassa TKKS melimpahmaka perlu suatu metode untuk meningkatkan kualitas dari TKKS dengan melakukan pengolahanawal. Torefaksi merupakan salah satu metode pengolahan awal untuk peningkatan kualitas biomassadengan temperatur proses sekitar 200-350 o C tanpa adanya oksigen. Setelah mengalami prosestorefaksi maka TKKS akan memiliki kandungan energi tinggi serta kemampuan menyerap air rendah.Dengan kemampuan menyerap air rendah maka TKKS dapat disimpan dalam rentang waktu lamapada kondisi kelembaban tinggi seperti Indonesia. Adapun variasi dalam penelitian ini yaitutemperatur antara 250-350 o C serta waktu tahan torefaksi antara 15-60 menit. Adapun analisa produkTKKS torefaksi yaitu analisa proksimat, kemampuan menyerap air, kandungan hemiselulosa dannilai kalor. Pada percobaan ini memperlihatkan bahwa pada temperatur torefaksi lebih tinggi sertawaktu tahan torefaksi yang lama akan meningkatkan kandungan energi serta menurunkankemampuan menyerap air tapi menghilangkan massa TKKS lebih banyak. Pada percobaan inikandungan energi dari TKKS dapat meningkat sekitar 30%Kata kunci: nilai kalor; TKKS;hemiselulosa; hidropobik; torefaksi